On the Cox ring of P^2 blown up in points on a line - Ottem, John Christian (Mathematica Scandinavica, 2011)
We show that the blow-up of P^2 in n points on a line has finitely generated Cox ring. We give explicit generators for the ring and calculate its defining ideal of relations.